Efektivitas Program Praktik Kerja Industri (Prakerin): Analisis Terhadap Implementasi dan Dampaknya dalam Meningkatkan Kesiapan Kerja Siswa - Febrianti, Novi; Darwin, Widya; Deswina, Melri; Jusmardi, Jusmardi (Universitas Lampung, 2023)
This study aims to describe the impact of implementing industrial work practices on student work readiness. The research method used is descriptive research with a quantitative approach. The research sample consisted of 43 students of class XII majoring in Computer and Network Engineering (TKJ) at SMK Negeri 2 Painan who had undergone industrial work practices. Data collected through questionnaires and documentation were analyzed using the product moment correlation method and simple linear regression. The results showed that there was a positive influence, although not significant, between the implementation of industrial work practices and student work readiness, indicated by a correlation coefficient (ryx) of 0.359 at a significance level of 5%. This shows that there is a significant impact between the implementation of the apprenticeship program and the readiness of students to enter the world of work at SMK Negeri 2 Painan. Furthermore, to determine the percentage contribution of variable X to Y, a determinant analysis is carried out. The coefficient of determination (r2) is 0.129, which means that the contribution of the apprenticeship program to the readiness of students to enter the world of work is 12.9%. Based on the descriptive analysis, the conclusion is that the readiness of students to enter the world of work has not yet reached an optimal level, with a percentage of 12.87% of students having a low level of preparation for work. Kata kunci: Dampak, Kesiapan Kerja, Praktik Kerja Industri